COMPREHENSIVE STRATEGY TO INCREASE AWARENESS AND COMPLIANCE WITH SAFETY PROCEDURES IN MRI EXAMINATIONS TO REALIZE SAFE AND QUALITY HEALTH SERVICES - Astri Kusuma Cahyani; Wahyu Sartika Dewi (Poltekkes Kemenkes Semarang, 2025)
ABSTRACTMagnetic Resonance Imaging (MRI) is a non-invasive diagnostic method that uses magnetic fields and radio waves to produce detailed images of the body. This procedure provides very significant benefits in the medical world, especially for detecting various health conditions. However, behind the benefits, there are potential safety risks that need to be well understood by medical personnel, patients, and patient companions. Awareness of these safety procedures is crucial to minimize the risk of injury or complications during the inspection. In one of the hospitals, the implementation of safety procedures involves providing comprehensive education to all relevant parties within the scope of MRI examination. This education includes an in-depth explanation of potential hazards, such as the interaction of metal objects with strong magnetic fields, as well as guidance on adhering to safety rules while in the MRI room. Medical personnel are also equipped with training designed to ensure compliance with safety protocols. The results of the study show that the level of awareness of MRI safety procedures still varies in various health facilities. Some facilities with good education and training programs show a higher level of awareness, while others require improvement in this regard. Efforts to raise awareness can be carried out through a combination of various approaches, including structured education, regular training for medical personnel, and the use of modern technology to support safety. With these measures, risks in MRI examinations can be minimized, resulting in a safe and effective examination environment.